Unusual isosymmetric order–disorder phase transition in a new perovskite-type dimethylhydrazinium manganese formate exhibiting weak ferromagnetism and photoluminescence properties. Issue 21 (14th May 2021) - Zienkiewicz, Jan Albert; Kowalska, Dorota Anna; Fedoruk, Katarzyna; Stefanski, Mariusz; Pikul, Adam; Ptak, Maciej
Abstract : We report the synthesis, thermal, structural, dielectric, magnetic and optical properties of a novel metal–organic framework templated by the large 1, 1-dimethylhydrazinium cation. We analyse the steric hindrance-related properties. Abstract : We report the synthesis and investigation of the physicochemical properties of a novel hybrid organic–inorganic formate perovskite templated by the unsymmetrical 1, 1-dimethylhydrazinium (DMHy + ) cation, [DMHy]Mn(HCOO)3 . This compound undergoes a first-order structural phase transition (PT) at 244.4 K (283.0 K) on cooling (heating) and both phases have the same monoclinic ( P 21 / n ) symmetry. Such isosymmetric PT is very unusual in the family of metal–formate frameworks and the X-ray diffraction and dielectric studies reveal that the PT is associated with ordering of the DMHy + cations, re-arrangement of hydrogen bonds and strong distortion of the manganese–formate framework. The DMHy + cation is the largest cation used so far for the synthesis of formate-based 3D perovskites. The comparison with other derivatives of hydrazinium-based analogues reveals that the increased steric hindrance, triggered by an increased number of methyl groups in the hydrazinium cation, affects the temperature and mechanism of the observed order–disorder PTs. We show that the temperature of the order–disorder PTs in this subgroup of compounds depends linearly on the effective ionic radius of organic cations, tolerance factor and number of disordered states. Magnetic studies indicate that [DMHy]Mn(HCOO)3 is a weak ferromagnet with the ordering temperature of 8.4 K. [DMHy]Mn(HCOO)3 exhibits pinkish photoluminescence under 266 nm excitation with the low activation energy of 62 meV. The emission lifetime reaches 157.6 μs at 80 K. The low activation energy and strong temperature-dependent photoluminescence suggest a potential application of [DMHy]Mn(HCOO)3 for non-contact temperature sensing below 200 K.